The Healthy Ageing Unit: Beyond discharge - Michael, Rene; Wichmann, Helen; Wheeler, B.; Horner, Barbara; Downie, Jill (Australasian Rehabilitation Nurses Association, 2005)
This article describes the final stage of a three-stage pilot research project conducted in a private hospital in Western Australia to examine the effectiveness and acceptability of a Healthy Ageing Unit. The Unit was based on a model of nurse-led intermediate care for the older acute patient. The objective of this stage was to review clinical outcomes of a sample of patients who had formed the intervention and control groups in Stage Two. The clinical outcomes included patient functional status and psychological well-being. Levels of patient satisfaction with the Unit, level of support required, confidence and re-admission rates were also examined. Eighty-one of the original 168 patients (48.2%) were followed-up at three-month post-discharge. Results revealed that at discharge the intervention group showed significantly greater improvement in levels of confidence and on the clinical outcomes measured, but that these improvements were not maintained at three-months. However, continued differences were still observed between the groups in relation to the level of support required by the groups. Specifically, 100% of the control group compared to 88% of the intervention group indicated that they still required support from external sources, such as the doctor, community services, family or friends. In addition, feedback from patients who formed the intervention group indicated a high degree of satisfaction with the Unit - with comments praising the model and particularly the support provided by the nurse-led, multidisciplinary, gerontological care team. The pilot study provided evidence of the positive impact and benefits of the Unit on patient outcomes beyond discharge.